The Effects Of Flipped Learning With Peer Instruction On Esl Students' Engagement And Reading Comprehension - Alhasani, Hani M.A. (2018)
This study examines the effects of flipped learning on enhancing ESL students' engagement and reading comprehension skills. A flipped learning - LMS- installed with the PowerPoint slides and materials on an online site was brought into classroom instructions used by peers for the benefit of effective teaching. A total of 170 samples, with 85 samples each, underwent a five-week, 2x2 factorial design experimental study. The effects of flipped learning only and with peer instruction (FLO, FLPI) as well as its associated moderating variable, language proficiency (high-low) and gender (malefemale) on students' engagement and reading comprehension were examined. Results from the analysis of Covariate (ANCOVA) show that students who underwent the FLPI mode outperformed students who underwent the FLO for adjusted mean difference of 4.052 similarly students from the FLPI given higher engagement score when compared to students from the FLO mode.